Exposure region of the Kawase approach and its correlation with skull base anatomy: An evaluation with digital models - Yan, Yong; Xu, Tao; Zhao, Yuqing; Mei, Qiyong; Jiang, Lei; Hou, Lijun (Frontiers in Surgery, 2023)
Kawase approaches is one of the most used trajectories in the skull base surgery. The exposure range of the approaches and its correlation with the skull base anatomy still demand more explorations. With the help of digital rebuilding, analyzing and measurement, we made an evaluation of the exposure range of the Kawase and extended Kawase approaches, and analyzed the correlation between the exposure range and the variants of the petrosal and clival anatomy. The finding of the study demonstrated that comparing to the sub-temporal approach, the Kawase approach and the extended Kawase approach significantly added the exposure range in the upper, middle, and partial inferior region of the clivus. The gains in the exposure volume and area are more when the manipulation angle is less than 135°.